2001
DOI: 10.1038/ni743
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis and anergy of CD4+CD25+ suppressor T cells in vivo

Abstract: CD4(+)CD25(+) suppressor T (TS) cells play a critical role in the maintenance of peripheral tolerance. We examined here proliferative and functional responses as well as differential gene expression in T(S) cells. We found that T(S) cells were hyporesponsive to antigenic stimuli in vivo and unable to flux Ca(2+) upon T cell receptor (TCR) engagement. However, T(S) cells were not impaired in their proliferative response to lymphopenia, which was dependent on major histocompatibility complex class II expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
487
5
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(534 citation statements)
references
References 71 publications
36
487
5
6
Order By: Relevance
“…This provides direct evidence for PD-1 as a negative regulator of immune responses in vivo [13]. PD-1 mRNA is expressed at high levels in CD4 + CD25 + regulatory T cells (Treg) and anergic T cells [14,15], suggesting the possible involvement of PD-1 in regulating Treg function and T cell tolerance.…”
Section: Introductionmentioning
confidence: 73%
“…This provides direct evidence for PD-1 as a negative regulator of immune responses in vivo [13]. PD-1 mRNA is expressed at high levels in CD4 + CD25 + regulatory T cells (Treg) and anergic T cells [14,15], suggesting the possible involvement of PD-1 in regulating Treg function and T cell tolerance.…”
Section: Introductionmentioning
confidence: 73%
“…T reg homeostasis requires continuous interaction with DC presenting self-peptide [19,21]. Recently, it has been shown that T reg proliferate in vivo vigorously in response to antigen stimulation [22], and that mature DC are responsible for such Ag-induced T reg proliferation [10], reverting the general belief that T reg constitute an anergic population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dependence on IL-2 for Treg maintenance is only seen in lympho-replete animals. IL-2 is dispensable for the expansion of Treg in a lymphopenic host, suggesting that there are at least two mechanisms involved in Treg expansion and survival [22,23].…”
Section: Introductionmentioning
confidence: 99%